1992
DOI: 10.7326/0003-4819-116-11-888
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension Predicts Mortality and Morbidity in Patients with Dilated Cardiomyopathy

Abstract: Noninvasive assessment of pulmonary hypertension using continuous-wave Doppler of tricuspid regurgitation can predict morbidity and mortality in patients with ischemic or idiopathic dilated cardiomyopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
175
0
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(185 citation statements)
references
References 28 publications
8
175
0
1
Order By: Relevance
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty full‐text articles were assessed for eligibility (Figure 1). Fifteen (8 RHC and 7 echocardiography) studies were included in the meta‐analysis 2, 3, 4, 5, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20. The characteristics of the included studies are shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Studies included in this analysis are Valerio et al,10 Heresi et al,11 Kovacs et al,5 Suzuki et al,12 Maron et al,3 Takahashi et al,13 Douschan et al,4 Assad et al,2 Abramson et al,14 Kjaergaard et al,15 Shalaby et al,16 Lam et al,17 Damy et al,18 Cabrita et al,19 and Choudhary et al 20. CI indicates confidence interval; M‐H, Mantel‐Haenszel; RHC, right heart catheterization.…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have reported that patients with HF qualified for HTx have poor survival and that PH has no additive influence on their prognosis [2,9,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…22) Possible mechanisms whereby pulmonary hypertension (PH) could negatively affect the prognosis of chronic HF (CHF) patients include progression of RV dysfunction due to increased afterload, and a negative effect of PH on neurohumoral activation. [31][32][33] In the presence of elevated RV preload or afterload, septic shock, coexistent with LV dysfunction or right coronary artery occlusive disease, the function of RV becomes hemodynamically significant. 34,35) We considered that RV function may determine afterload such as PH and proper contractive ability.…”
Section: )mentioning
confidence: 99%